2017
DOI: 10.1155/2017/7842413
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response of Soft Core Sandwich Beams with Metal-Graphene Nanocomposite Skins

Abstract: Sandwich structures are able to provide enhanced strength, stiffness, and lightweight characteristics, thus contributing to an improved overall structural response. To this sandwich configuration one may associate through-thickness graded core material properties and homogeneous or graded properties nanocomposite skins. These tailor-made possibilities may provide alternative design solutions to specific problem requisites. This work aims to address these possibilities, considering to this purpose a package of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Otherwise, to perform free vibration analysis, only the load vector will be null. Assuming free harmonic vibrations, the equilibrium equation will become Equation ( 14) [31,34,35]:…”
Section: Displacement Field and Equilibrium Equationsmentioning
confidence: 99%
“…Otherwise, to perform free vibration analysis, only the load vector will be null. Assuming free harmonic vibrations, the equilibrium equation will become Equation ( 14) [31,34,35]:…”
Section: Displacement Field and Equilibrium Equationsmentioning
confidence: 99%
“…The authors also provided a summary and an outlook on foreseen potential developments in the field. The impact on the viscoelastic behavior of sandwich structures by integrating through-thickness graded core materials and nanocomposite skins with homogeneous or graded properties where the viscoelastic behavior of the sandwich core was modeled using the complex method was investigated by Loja [18]. It was concluded that effective design solutions for specific structural requirements can be achieved by considering such material design variables/profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of vibrations is advantageous in several mechanical systems, since it allows an increase in the service life and a reduction in its weight. In a previous work [7], Loja studied, among others, a sandwich beam with graded metal-graphene nanocomposites skins and a soft core, since soft and lightweight cores allow a viscoelastic damped behavior. This kind of behavior is of great interest in most engineering applications not only because it is responsible for the vibration attenuation but also for greater fatigue and impact resistance.…”
Section: Introductionmentioning
confidence: 99%